2013
DOI: 10.1128/jvi.00462-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Suppressor Mutation That Improves the Yields of Hexon-Modified Adenovirus Vectors

Abstract: We have generated hexon-modified adenovirus serotype 5 (Ad5) vectors that are not neutralized by Ad5-specific neutralizing antibodies in mice. These vectors are attractive for the advancement of vaccine products because of their potential for inducing robust antigen-specific immune responses in people with prior exposure to Ad5. However, hexon-modified Ad5 vectors displayed an approximate 10-fold growth defect in complementing cells, making potential vaccine costs unacceptably high. Replacing hypervariable reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…S4 ). For both Ad5-37(5, 7) and Ad5-43(5, 7), the level of genome replication and the expression of late adenovirus proteins were similar to that of Ad5 at all time points 20 . However, productivity of these vectors showed remarkable differences at all times compared to Ad5.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…S4 ). For both Ad5-37(5, 7) and Ad5-43(5, 7), the level of genome replication and the expression of late adenovirus proteins were similar to that of Ad5 at all time points 20 . However, productivity of these vectors showed remarkable differences at all times compared to Ad5.…”
Section: Resultsmentioning
confidence: 83%
“…These results indicated the presence of other factors which could affect the hexon trimer formation. Thus far, several studies have reported the growth defect among chimeric adenovirus vectors 20 40 , and the authors posed the following reasons for these deficiencies in replication: 1) severe retardation of hexon folding into trimers which can delay the virus replication cycle; 2) antipathy of other major capsid proteins for the chimeric hexon, thereby causing stagnation of protein packing during virus assembly and production of progeny virus. However, the precise mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates were serially passaged in this manner every 3 days until CPE was observed. The identity of the adenovector was determined using primers Ad5s278 (CGCGGGAAAACTGAATAAGA) and Ad5a3598 (GCTGCTGCAAAACAGATACA) as indicated in Figure 2 B. Vector yields were determined by using the ffu assay 60 on a subset of approximately 10% of the array to ensure that sufficient quantities of vector were being produced.…”
Section: Methodsmentioning
confidence: 99%
“… 58 , 101 Here, the identification of a single suppressor mutation in the hexon sequence that allowed for HAdV-5 vector HVR chimeras to be manufactured with near wild-type vector yields has fueled the generation of HVR chimeric vectors. 102 At present, a vaccine candidate against HIV, based on a HAdV-5 vector carrying the HVR domains from HAdV-48, has been shown to be both safe and immunogenic. 103 The i.v.…”
Section: Alternatives To Hadv-5 Vectorsmentioning
confidence: 99%